Effects of L-theanine on Anxiety-like Behavior, Cerebrospinal Fluid Amino Acid Profile, and Hippocampal Activity in Wistar Kyoto Rats (P14-022-19) - Ogawa, Shintaro (Curr Dev Nutr, 2019)
OBJECTIVES: L-theanine (N-ethyl-L-glutamine), an amino acid is well known as a relaxing agent. In the present study, we examined the effects of repeated L-theanine administration on behavior, hippocampal activity in Wistar Kyoto (WKY) rats, levels of amino acids in the cerebrospinal fluid (CSF), and studied an animal model of anxiety and depressive disorders. METHODS: Behavioral tests were performed after 7–10 days of L-theanine (0.4 mg kg(−1) day(−1)) or saline administration, followed by CSF sampling for high-performance liquid chromatography (HPLC) analysis. An independent set of animals was subjected to [18F] fluorodeoxyglucose positron emission tomography (PET) scanning after an identical dose of L-theanine or saline administration for 7 days. RESULTS: In an elevated plus maze test, the time spent in open arms was significantly longer in the L-theanine group compared to saline group (P = 0.035). Also, significantly lower CSF glutamate (P = 0.039) and higher methionine (P = 0.024) concentrations were observed in the L-theanine group. Further, a significant increase in the standard uptake value ratio was observed in the hippocampus/cerebellum of the L-theanine group (P < 0.001). CONCLUSIONS: These results suggest that L-theanine enhances hippocampal activity and exerts anxiolytic effects, which may be mediated by changes in glutamate and methionine levels in the brain. However, further study is required to effectively elucidate the mechanisms underlying the effects of L-theanine. FUNDING SOURCES: This research study was funded by an unrestricted research grant provided by Taiyo Life Insurance, Himawari Foundation, Tokyo, Japan.